Strategi Kepemimpinan Kepala Sekolah Dalam Supervisi Pembelajaran Guru Pendidikan Agama Islam Di SMPN 1 Petasia Kabupaten Morowali Utara - Surani Surani; Annisa Saputri; Mustamin Mustamin (Universitas Muslim Indonesia, 2022)
This study discusses the ''Leadership Strategy of the Principal in Supervision of Islamic Religious Education Learning at SMPN 1 Petasia, North Morowali Regency'' with the main problems located in: (1) How is the technique of vital authority in directing Islamic learning? Educational Educators at SMPN 1 Petasia (2) What are the elements that hinder and support vital initiative procedures in conducting learning management for madrasah teachers at SMPN 1 Petasia. This study is expected to be able to decide on the leading initiative technique in supervising Islamic Religious Education educators at SMPN 1 Petasia, North Morowali Regency. This type of examination uses a fascinating subjective technique approach. The strategies used in gathering information are perception, meeting, documentation, and triangulation. The consequences of this review show that the methodology used by school principals in supervising the learning of Islamic Religious Education teachers is very large, namely based on their duties and responsibilities as school principals, deliberation in making decisions, applying discipline, using a democratic type or style of leadership. , also uses techniques namely individual supervision, direct supervision and roundabout, and gathering supervision. The inhibiting variables seen by the principal in carrying out supervision are the main administrative obligations which are very thick with the aim of managing and cannot be carried out routinely differences in beliefs, and management. carried out during the pandemic only in the form of reports. The supporting factors for school principals in carrying out supervision are infrastructure facilities and administrative completeness.